2007
DOI: 10.1002/ijc.22800
|View full text |Cite
|
Sign up to set email alerts
|

Microrna expression distinguishes between germinal center B cell‐like and activated B cell‐like subtypes of diffuse large B cell lymphoma

Abstract: Diffuse large B cell lymphoma (DLBCL) is an aggressive malignancy that accounts for nearly 40% of all lymphoid tumors. This heterogeneous disease can be divided into germinal center B celllike (GCB) and activated B cell-like (ABC) subtypes by gene expression and immunohistochemical profiling. Using microarray analysis on prototypic cell lines, we identified microRNAs (miR-155, miR-21 and miR-221) that were more highly expressed in ABC-type than GCB-type cell lines. These microRNAs were over-expressed in de nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
347
3
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(385 citation statements)
references
References 33 publications
32
347
3
3
Order By: Relevance
“…By contrast to the findings of the present study, Lawrie et al (21) identified miR-21, miR-155 and miR-221 as discriminatory between ABC and GC with higher expression seen in ABC-type cell lines and also in patient material. miR-21 and miR-155 were confirmed to differentiate between ABC-and GC-like cell lines by another group (20).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…By contrast to the findings of the present study, Lawrie et al (21) identified miR-21, miR-155 and miR-221 as discriminatory between ABC and GC with higher expression seen in ABC-type cell lines and also in patient material. miR-21 and miR-155 were confirmed to differentiate between ABC-and GC-like cell lines by another group (20).…”
Section: Discussioncontrasting
confidence: 99%
“…This was most likely due to technical differences including sample preparation, array platforms and the control population used. Moreover, all three studies used a variety of cell lines with little or no overlap; one ABC and one GC type was common between the present investigation and Malumbres et al (20) and 2 GC types were used by both Lawrie et al and this study (21). Also, it is worth mentioning that the total number of microRNAs analysed in the present study was significantly higher than the previous two investigations (20,21) (420 vs 225 and 217, respectively) thus, including many more microRNAs which are differentially expressed between the DLBCL subgroups.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…After manually screening the titles, abstracts and key data, 259 records were excluded for not meeting the criteria listed above. Of the 28 reports selected for the systematic review, 12 studies were excluded in the final meta-analysis for lack of key HR value [21][22][23][24][25][26][27][28][29][30][31][32]. The excluded 12 studies commonly focused on other miRNAs and did not analyze the miR-155 data individually.…”
Section: Resultsmentioning
confidence: 99%